Regulating smart contracts: the future of contract law or simply technical innovation - Vasiļevska, Alīna (Riga Graduate School of Law, 2022)
While the development of global smart contracts’ market size is forecasted to reach USD 300 million by 2023, in comparison with USD 144.95 million in 2020, legally smart contracts remain a challenging area of contract law.1 The desire of states to create a legislative framework for smart contracts, thus willing to attract investors, develop digital financial assets and the country’s economy as a whole, but at the same time, the lack of research carried out in the field of smart contracts regulation highlight the topicality of this research. The study addresses the issues of forming a system of legal regulation of a smart contract and determines its place in modern contract law. By analysing the existing theoretical and legal framework of smart contracts in the European Union and beyond, the study aims to formulate recommendations on the prospects for legislative regulation of smart contracts and their implementation into legal reality. The results indicate that a smart contract can be considered as the new form of a digital contract and there are no major obstacles for its application within the existing legal framework, nevertheless, the concept of the smart contract still needs to be further defined more clearly and specifically at the legislative level since insufficiently thought-out regulation will hide the development of this phenomenon.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Contract law; Smart contracts; Blockchain